Viscosity Measurements of Dilute Poly(2-ethyl-2-oxazoline) Aqueous Solutions Near Theta Temperature Analyzed within the Joint Rouse-Zimm Model - Jana Tóthová; Katarína Paulovičová; Vladimír Lisý (International Journal of Polymer Science)
The steady-state shear viscosity of low-concentrated Poly(2-ethyl-2-oxazoline) (PEOX) aqueous solutions is measured near the presumed theta temperature using the falling ball viscometry technique. The experimental data are analyzed within the model that joins the Rouse and Zimm bead-spring theories of the polymer dynamics at the theta condition, which means that the polymer coils are considered to be partially permeable to the solvent. The polymer characteristics thus depend on the draining parameter h that is related to the strength of the hydrodynamic interaction between the polymer segments. The Huggins coefficient was found to be 0.418 at the temperature 20°C, as predicted by the theory. This value corresponds to h = 2.92, contrary to the usual assumption of the infinite h. This result indicates that the theta temperature for the PEOX water solutions is 20°C rather than 25°C in the previous studies. The experimental intrinsic viscosity is well described coming from the Arrhenius equation for the shear viscosity.